Discrete flight path angle tracking control of hypersonic flight vehicles via multi-rate sampling - Xu, Bin (2013)
This paper presents the flight path angle tracking control of the longitudinal dynamics of a generic hypersonic flight vehicle(HFV). Due to the use of digital computers and microprocessors for controls applications, the discrete hypersonic flight control is investigated. The altitude command is transformed into the flight path angle information. The back-stepping scheme is applied for the attitude subsystem which includes flight path angle, pitch angle and pitch rate. The virtual control is designed with nominal feedback and Neural Network (NN) approximation. To use the information of throttle setting, the multi-rate sampling method is employed for the two subsystems where the velocity subsystem is considered as slow dynamics. Under the proposed controller, the semiglobal uniform ultimate boundedness (SGUUB) stability is guaranteed. The simulation is presented to show the effectiveness of the proposed control approach.